The immunological evaluation of levamisole treatment in cancer patients. Issue 638 (December 1978) - Verhaegen, H.; de Cree, J.; de Beukelaar, A.; de Cock, W.; Verbruggen, F.; Krug, F.
Abstract : The effect of levamisole on different immunological parameters was studied in patients with various malignant diseases. Levamisole restored tuberculin-negative delayed hypersensitivity reactions and increased the sensitivity to 1-nitro-2, 4-dichlorobenzene challenges. It also increased low E-rosette formation of T-lymphocytes and enhanced the clearance of a lipid emulsion by the reticulo-endothelial system. Levamisole had no effect on serum immunoglobulin levels but increased serum haemolytic complement activity.